О равномерной сходимости рядов Фурье к (ψ, β)-производным - Радзиевская, Елена Ивановна (My University, 2018)
In terms of the best approximations of a function in the space Lp, the condition for the existence of (ψ, β) -derivatives and uniform convergence of the Fourier series to them is found.
Keywords: кафедра вищої математики імені проф. Можара В. І.; ψ, β-производные; равномерная сходимость рядов Фурье; приближения функции; пространства Lp; ψ, β-derivatives; uniform convergence of Fourier series; approximations of a function; Lp spaces